Children's Crusade for Children records - Children's Crusade for Children
Correspondence, drafts of speeches and articles by Dorothy Canfield Fisher and others, clippings, administrative records, requests for public support, and publicity materials used in the crusade to aid refugee children of Europe through the contribution of money from American school children. Correspondents include Marion G. Canby, Dorothy Canfield Fisher, John Herling, Herbert H. Lehman, and William Allen White.
Organization formed in 1939-1940 by Marion G. Canby and Dorothy Canfield Fisher to aid the war-exiled children of Europe.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Canby, Marion G. -- 1885-1974 -- Correspondence; Fisher, Dorothy Canfield, -- 1879-1958.; Fisher, Dorothy Canfield, -- 1879-1958 -- Correspondence; Herling, John -- Correspondence; Lehman, Herbert H. -- 1878-1963 -- Correspondence; White, William Allen, -- 1868-1944 -- Correspondence; World War, 1939-1945 -- Children; World War, 1939-1945 -- Civilian relief; World War, 1939-1945 -- Refugees